Genome-Wide and Candidate Gene Association Analyses Identify a 14-SNP Combination for Hypertension in Patients With Type 2 Diabetes. (4th December 2020) - Cheng, Chi-Fung; Hsieh, Ai-Ru; Liang, Wen-Miin; Chen, Ching-Chu; Chen, Chien-Hsiun; Wu, Jer-Yuarn; Lin, Ting-Hsu; Liao, Chiu-Chu; Huang, Shao-Mei; Huang, Yu-Chuen; Ban, Bo; Lin, Ying-Ju; et al.
Abstract: Background: High blood pressure is common and comorbid with type 2 diabetes (T2D). Almost 50% of patients with T2D have high blood pressure. Patients with both conditions of hypertension (HTN) and T2D are at risk for cardiovascular diseases and mortality. The study aim was to investigate genetic risk factors for HTN in T2D patients. Methods: This study included 999 T2D (cohort 1) patients for the first genome scan stage and 922 T2D (cohort 2) patients for the replication stage. Here, we investigated the genetic susceptibility and cumulative weighted genetic risk score for HTN in T2D patients of Han Chinese descent in Taiwan. Results: Thirty novel genetic single nucleotide polymorphisms (SNPs) were associated with HTN in T2D after adjusting for age and body mass index ( P value <1 × 10 −4 ). Eight blood pressure-related and/or HTN-related genetic SNPs were associated with HTN in T2D after adjusting for age and body mass index ( P value <0.05). Linkage disequilibrium and cumulative weighted genetic risk score analyses showed that 14 of the 38 SNPs were associated with risk of HTN in a dose-dependent manner in T2D (Cochran–Armitage trend test: P value <0.0001). The 14-SNP cumulative weighted genetic risk score was also associated with increased regression tendency of systolic blood pressure in T2D (SBP = 122.05 + 0.8 × weighted genetic risk score; P value = 0.0001). Conclusions: A cumulative weighted genetic risk score composed of 14 SNPs is important for HTN, increased tendency of systolic blood pressure, and may contribute to HTN risk in T2D in Taiwan. Graphical Abstract: